2012
DOI: 10.1002/asia.201200450
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen‐Bonding Interactions and Properties of Energetic Nitroamino[1,3,5]triazine‐Based Guanidinium Salts: DFT‐D and QTAIM Studies

Abstract: The intramolecular hydrogen-bonding interactions and properties of a series of nitroamino[1,3,5]triazine-based guanidinium salts were studied by using the dispersion-corrected density functional theory method (DFT-D). Results show that there are evident LP(N or O; LP = lone pair)→σ*(N-H) orbital interactions related to O⋅⋅⋅H-N or N⋅⋅⋅H-N hydrogen bonds. Quantum theory of atoms in molecules (QTAIM) was applied to characterize the intramolecular hydrogen bonds. For the guanidinium salts studied, the intramolecul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 84 publications
0
6
0
Order By: Relevance
“…The hydrogen bond plays an important role in increasing the density and decreasing the sensitivity of energetic compounds 50 , 51 . The structures of [Gly]ClO 4 and [Ala]NO 3 were characterized by single-crystal X-ray diffraction (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The hydrogen bond plays an important role in increasing the density and decreasing the sensitivity of energetic compounds 50 , 51 . The structures of [Gly]ClO 4 and [Ala]NO 3 were characterized by single-crystal X-ray diffraction (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…[10][11][12] In order to comprehensively reveal the effects of conformations on intramolecular interactions and stability, various intramolecular interactions were predicted and results are tabulated in table 2, the variation trends of these parameters are plotted in figure 2.…”
Section: Intra-molecular Interactionsmentioning
confidence: 99%
“…Previous studies have shown that orbital interaction diagrams can reflect the relationships between the orbitals of salts and the isolated ions. [10][11][12] The orbital figure 5. Figure 5 clearly shows the contributions from the orbitals of the isolated anion and cation to the orbitals of salts.…”
Section: Chemical and Uv Stabilitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…, the LUMO (lowest unoccupied molecular orbital) of TNAD has lower energy than TNAZ and TNAD has a slightly higher Δ E g (5.22 eV) than TNAZ (5.06 eV). According to the previous study, TNAD should have a slightly lower chemical reactivity than TNAZ. And for TNAD and TNAZ, the atomic orbitals of C and N in the skeleton all participate in HOMO (highest occupied molecular orbital), but not LUMO.…”
Section: Stabilitymentioning
confidence: 99%